Ikon Tradisi Ba’do Katupat sebagai Refleksi Kebudayaan Masyarakat Jaton di Sulawesi Utara - Djojosuroto, Kinayati (el Harakah: Jurnal Budaya Islam, 2013)
Ba’do Katupat celebration is a tradition of Jawa Tondano (Jaton) village hold annually. It has a deep meaning to strengthen the relationship, forgive each other, as well as be grateful  for the success of fasting for the whole month. No wonder the celebration is always crowded with thousands of people from different areas, ages and beliefs, and carried out for the whole day. Ba’do Ketupat is an inherited tradition from Diponegoro, Kiai Mojo, and his followers. This Javanese tradition heritage can be found in Tondano, Minahasa as a ceremonial event held annually by people in Jaton village one week after Eid  Ba’do Ketupat contains cultural values   that include local and cultural values, as the icon and identity of  Jaton in Minahasa, as well as the acculturation resulting in solidarity and tolerance. This culture unites the minority of Jaton people with the majority of Minahasa people. The religious ritual performed by Jaton people and other Muslim accomplishes religious obligations in order to increase devotion towards Allah SWT and not to create difference. Perayaan Ba’do Katupat merupakan tradisi kampung Jawa Tondano yang dilaksanakan setiap tahun. Acara ini memiliki makna yang mendalam yaitu untuk memperkokoh tali silaturahim, bermaaf-maafan, sekaligus ucapan syukur atas keberhasilan menjalankan ibadah puasa sebulan lamanya. Tak heran perayaan tersebut selalu dipadati ribuan masyarakat dari berbagai daerah, usia dan keyakinan dan berlangsung sejak pagi hingga malam hari. Ba’do Katupat merupakan tradisi yang diwariskan Diponegoro, Kiai Mojo dan pengikut - pengikutnya. Tradisi ini adalah warisan tradisi Jawa yang ada di Tondano Minahasa dan menjadi acara seremonial yang setiap tahun diselenggarakan warga di Kampung Jaton setelah lewat satu minggu lebaran. Ba’do Katupat mengandung nilai-nilai budaya yang mencakup kearifan lokal dan kearifan budaya Jaton, sebagai ikon dan identitas warga Jaton di Minahasa, serta sebagai akulturasi budaya sehingga terjadi solidaritas dan toleransi. Budaya tersebut mempersatukan penduduk minoritas Jaton dengan penduduk mayoritas Minahasa. Ritual keagamaan yang dilakukan oleh orang Jaton maupun Muslim yang lain merupakan pelaksanaan kewajiban agama dalam upaya meningkatkan ketakwaan kepada Allah SWT dan bukan menciptakan perbedaan.